Comparing the Fears of Children With and Without Significant Disabilities - Burnham, Joy J.; Mutua, Kagendo; Tallent, Desiree’ A.; Robinson, Olivia P.; Bledsoe, Kenya G.; Davis, Amy P. (Canadian Journal of Counselling and Psychotherapy, 2018)
Although research on children’s fears is available, there is a gap in the literature concerning the fears of children with disabilities. We used the Fear Survey Schedule for Children (FSSC-AM; Burnham, 2005) to examine age, racial, and gender differences of 404 children (ages 7–20), including 50% with disabilities and 50% without disabilities. Significant fear differences were reported across gender, age, race, and disability. For example, children with intellectual disabilities had more fears related to safety. Both younger and older children with moderate to profound disabilities had significantly more fear than their peers without disabilities. This study broadened the examination of fears in children with moderate, severe, and profound disabilities.